Impact of Conservation Agriculture on Corm Quality of Elephant foot yam Intercropped in Banana - Remya, K; Suja, G (JOURNAL OF ROOT CROPS, 2018)
On-station and on-farm field experiments were conducted separately in series for three years during 2014-2017, to develop and validate resource conservation technologies for elephant foot yam in banana based system. In the on-station field experiment conducted at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala, the effect of five treatments viz., conservation organic, conservation chemical, conventional chemical, conventional (package of practices (POP) as control) and organic management + conventional tillage were replicated four times in RBD. In the on-farm trial conducted in farmer‘s field at Alathara, Kattela, Thiruvananthapuram, Kerala, four varieties of elephant foot yam (Gajendra, Sree Padma, Sree Athira and Peerumade Local) were tested under two practices viz., farmer’s practice (FP) and conservation chemical (CA) practice, replicated thrice in split plot design, with varieties in main plots and practices in sub plots.This paper reports the impact of conservation vs conventional agriculture vs farmer’s practice on corm biochemical and mineral composition. The bio-chemical constituents of corm was not significantly affected by the management options both in the on-station and on-farm experiments indicating the equal efficiency of conservation agriculture to the existing conventional or farmers practices. Among the varieties, the corm proximate composition of Gajendra var. excelled with significantly higher starch, total sugar and crude fibre contents. Among the interactions, Gajendra var. of elephant foot yam intercropped with banana under conservation practice had higher starch and sugar contents in corms. All the varieties, irrespective of practices, except Sree Athira under CA, produced corms with higher crude protein content.The oxalate content was significantly the lowest in Sree Padma under CA and Gajendra under FP. The various management options did not significantly affect the mineral composition of corms, except Ca, Mg and Cu contents. The Ca and Mg contents of corms were significantly higher in conservation chemical and conservation organic practices respectively. The above result was further confirmed in the on-farm validation trial. It can be inferred that conservation agriculture is a safe alternative to the existing practices in elephant foot yam as the bio-chemical and mineral contents were not significantly altered.